2017
DOI: 10.1073/pnas.1620674114
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying the landscape drivers of agricultural insecticide use leveraging evidence from 100,000 fields

Abstract: Agricultural landscape intensification has enabled food production to meet growing demand. However, there are concerns that more simplified cropland with lower crop diversity, less noncrop habitat, and larger fields results in increased use of pesticides due to a lack of natural pest control and more homogeneous crop resources. Here, we use data on crop production and insecticide use from over 100,000 field-level observations from Kern County, California, encompassing the years 2005-2013 to test if crop divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 33 publications
1
51
0
Order By: Relevance
“…Nevertheless, further analysis would require setting species-specific survival thresholds to reflect that the minimum viable population highly depends on species attributes and environmental conditions. See Larsen and Noack (2017) for an example where responses to agricultural practices depend more on individual attributes (of both crops and pests) than on landscape characteristics.…”
Section: Survival Thresholdmentioning
confidence: 99%
“…Nevertheless, further analysis would require setting species-specific survival thresholds to reflect that the minimum viable population highly depends on species attributes and environmental conditions. See Larsen and Noack (2017) for an example where responses to agricultural practices depend more on individual attributes (of both crops and pests) than on landscape characteristics.…”
Section: Survival Thresholdmentioning
confidence: 99%
“…As land consolidation in China proceeds, there is a need to examine the effects of land consolidation on pesticide use. Ecological theory predicts that simplified agricultural landscapes will increase pest severity because fewer natural enemies and concentrated host plants will further increase pesticide use (Larsen & Noack, 2017). However, the role of the landscape in pesticide applications has not been adequately supported by empirical studies, partially due to the lack of high spatial resolution crop and insecticide data (Larsen & Noack, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ecologists have argued that landscape patterns influence pesticides because simplified landscapes often lead to increased pest severity, which leads to higher pesticide demand (Larsen, 2013; Larsen & Noack, 2017; Meehan, Werling, Landis, & Gratton, 2011). Agricultural intensification has caused landscape simplification due to the expansion of agricultural land, enlargement of field size, and removal of noncrop habitat.…”
Section: Introductionmentioning
confidence: 99%
“…A landscape dominated by non‐crop habitats is usually characterized by a higher abundance of natural enemies, and different non‐crop habitats in a landscape may serve varied functions for natural enemies at one or several times of the year . In recent decades, natural habitats in agricultural ecosystems have been degraded worldwide, with a corresponding reduction in the biological control services provided by natural enemies, leading to the need for increased agricultural input to control pests …”
Section: Introductionmentioning
confidence: 99%
“…10,11,14,15 In recent decades, natural habitats in agricultural ecosystems have been degraded worldwide, with a corresponding reduction in the biological control services provided by natural enemies, leading to the need for increased agricultural input to control pests. [16][17][18][19][20][21] Recent studies have suggested that the positive effects provided for natural enemies by non-crop habitats in a landscape can sometimes be affected (and even overridden) by agricultural practices. 9,15,[22][23][24][25][26] The use of chemical insecticides is one common agricultural practice that plays a crucial role in the regulation of pest insect densities, and often has lethal or sublethal effects on the natural enemies of key pests.…”
Section: Introductionmentioning
confidence: 99%